The administration of the school plants in the three districts of Camiling, Division of Tarlac - Clemente, Glicerio T. 1928- (s.n.], 1974)
This study looked into the problems and problem-solving practices in the administration and improvement of the plants in 33 public elementary schools in 3 districts on the basis of data from 351 respondents composed of 321 elementary school teachers, 4 teachers in charge, 9 head teachers, 14 principals, 3 district supervisors, 1 division industrial arts supervisor, 1 civil engineer, and 1 municipal treasurer. The common administrative problems met by the school heads are lack of (1) funds for school improvements or projects; (2) basic textbooks and teaching guides for all grades; and (3) classroom devices such as science apparatus, maps, radios, films, recorders, and other audiovisual equipment and facilities. The PTA, civic spirited citizens, the barrio council, civic organizations, government officials, teachers, and parents of graduating honor pupils are approached for donations of cash, material or labor for school projects.